To evaluate the expression 7s^2 when s = 4, we substitute the value of s into the expression.
7(4)^2 = 7(16) = 112
Therefore, the answer is 112.
evaluate the expression 7s^2 if s = 4
56
112
192
742
3 answers
show proof
Sure, here's the proof:
Given the expression 7s^2, we substitute s = 4 into the expression.
7(4)^2 = 7(16)
Next, we simplify the expression by computing the exponent:
7(16) = 112
Therefore, when s = 4, the expression 7s^2 equals 112.
Given the expression 7s^2, we substitute s = 4 into the expression.
7(4)^2 = 7(16)
Next, we simplify the expression by computing the exponent:
7(16) = 112
Therefore, when s = 4, the expression 7s^2 equals 112.